PENGARUH BIAYA PRODUKSI DAN PENJUALAN TERHADAP KINERJA KEUANGAN PADA PT. PERKEBUNAN NUSANTARA IV MEDAN - Siswanto Siswanto (Prodi Magister Manajemen Fakultas Ekonomi dan Bisnis Universitas Bhayangkara Jakarta Raya, 2023)
AbstractProduction costs are the costs incurred to process raw materials into finished products that are ready for sale. Sales are income transactions in the form of goods or services sent by customers to get cash to respect the obligation to pay. This study aims to determine the effect of production and sales costs on the gross profit of PT. Perkebunan Nusantara IV Medan. the type of research used is quantitative, the data used is the company's income statement and cost of goods from 2017 to 2019. The data sources used are primary data and secondary data. Primary data is data that comes from original or first sources and secondary data is data that is already available so that it can search for and collect data. The data obtained were then analyzed using the classical assumption test, normality test, multicollinearity test, autocorrelation test, multiple linear regression, partial test, simultaneous test, and the R-square coefficient of determination test. The results of the study concluded that the production costs tcount> ttable (-3.859> 2.03452) and sig <0.05 (0.01 <0.05) so it can be concluded that production costs have a negative and significant effect on financial performance. Then H0 is accepted, Ha is rejected. For sales, the value of tcount> ttable (2.146> 2.03452) and sig <0.05 (0.01 <0.05) so it can be concluded that sales have a positive and significant effect on financial performance. Then H0 is accepted Ha is rejected.